Malignant progression and recurrence rates following endoscopic treatment of gastric hyperplastic polyps - Turkot, Maryla H; Zaborowska, Marta; Pilonis, Nastazja D; Lenarcik, Małgorzata; Mróz, Andrzej; Wojciechowska, Urszula; Didkowska, Joanna; Rupinski, Maciej; Regula, Jaroslaw; Kaminski, Michal F; Januszewicz, Wladyslaw (Endoscopy, 2025)
Evidence supporting management algorithms for gastric hyperplastic polyps (GHPs) remains insufficient. To reassess the treatment criteria for these lesions, we analyzed the rate of neoplastic progression and recurrence after endoscopic resection.This retrospective study from a high-volume center included all patients diagnosed with GHPs between 2003 and 2022. We cross-referenced patient records with the National Cancer Registry to identify cases of subsequent gastric cancer, irrespective of endoscopic management. We evaluated the prevalence of neoplastic components within resected GHPs and examined associated risk factors. Finally, we assessed the local recurrence rate at endoscopic follow-up in patients who underwent endoscopic resection.889 patients were included (mean age 63.5 years; 66.9% female), with a median polyp size of 4 mm (interquartile range [IQR] 3-8 mm). Over a median follow-up of 30.5 months (IQR 11.1-61.2), gastric cancer developed in three patients (0.3%), yielding a cumulative incidence of 1.37% (95%CI 0.43%-4.30%). Of the 515 resected GHPs, neoplasia was found in 6 (1.2%), all measuring ≥20 mm and predominantly (5/6) with pedunculated morphology. Patient age (odds ratio [OR] 1.15, 95%CI 1.01-1.36; P = 0.04) and polyp size (OR 1.19, 95%CI 1.11-1.30; P < 0.001) were associated with neoplasia. Among 167 patients (32.4%) with follow-up data, 42 (25.1%) developed local recurrence.The risk of malignant progression in GHPs is low, while local recurrence after endoscopic resection remains notable. Endoscopic treatment should be prioritized for pedunculated polyps ≥20 mm, as these are more likely to harbor neoplasia.